CORPORATE SOCIAL RESPONSIBILITY AND INTELLECTUAL CAPITAL TO FINANCIAL PERFORMANCES IN THE IDX STATE-OWNED 20 INDEX - Suripto Suripto; João LuÃs Lucas (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to determine the influence of Corporate Social Responsibility (CSR) and Intellectual Capital as measured by Value Added Capital Employed (VACA), Value Added Capital Employed Human Capital (VAHU), and Structural Capital Value Added (STVA) on the Financial Performance of Companies. This type of research is associative quantitative using saturated samples, where all populations are used as samples, containing total of 20 State-owned Companies (SoC). While the research period was carried out over five years, namely 2018-2021, so there were 80 observational data. This study uses annual financial reports, sustainability reports, and company websites as secondary data sources sources then the researchers present the data in a data tabulation. Data analysis methods used in this study include descriptive statistics, classical assumptions, panel data regression, and hypothesis testing with Eviews-12 software. The results of this study indicate that the CSR and Intellectual Capital, as measured by VACA and STVA, significantly influence the financial performance of IDXSoC. However, VAHU does not influence financial performance. This study contributes to enriching the research development of the sustainability accounting field. Meanwhile, the results of this study may suggest that the SoC management should optimize CSR and Intellectual Capital performance in order to strengthen their financial performances.